EFEKTIVITAS INFUSA DAUN JAMBU BIJI (Psidium guajava) SEBAGAI PRESERVATIF ALAMI PADA KARKAS PUYUH - Eulis Tanti Marlina; Ellin Harlia; Yuli Astuti Hidayati; Deden Zamzam Badruzzaman; Wowon Juanda (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
Guava leaves can be used as a natural preservative in quail carcass because they contain antimicrobial compounds such as flavonoid and tannin. This study studied the effect of using guava leaves infusion on quail carcass on the total bacteria, Enterobacteriaceae, and early spoilage. The research used an experimental method with a completely randomized design, 3 treatments of guava leaves infusion concentration, namely P1 = 25%, P2 = 50%. And P3 = 75%, each treatment was repeated 6 times. The application of infusion to quail carcass was carried out by immersion for 15 minutes. Data were analyzed using ANOVA and Turkey’s test. The results showed that the total bacteria and Enterobacteriaceae before immersion were 3.80 x 107 cfu/g and 1.90 x 104 cfu/g, respectively. Soaking quail carcass in guava leaves infusion was able to reduce the total bacteria and Enterobacteriaceae to 72.15% and 78.50%, respectively. The early spoilage was inversely proportional to the total bacteria and Enterobacteriaceae resulted in longer shelf life.